Propiedades funcionales y nutricionales de seis especies de Pasiflora (Passifloraceae) del departamento del Huila, Colombia (2014)
ABSTRACT: We analyzed the functional and nutritional properties of six species of Passiflora (Passifloraceae) based on the uses reported by 74 farm families of ten municipalities of the Department of Huila in Colombia. The Ethnobotanical study allowed us to record 92 uses, most of which were medicinal, followed by the use of fruits for food. The phytochemical analysis of four species with the largest number of medicinal uses revealed the presence of phenolic compounds, triterpenes, steroids, and flavonoids, which would justify some of the uses reported by farmers. The nutritional analysis indicates that some of the fruits of Passiflora are high in Magnesium and Zinc, low in sodium, and have digestive properties.